The politics of Aboriginal title in British Columbia: from the Referendum to the Truth and Reconciliation Commission - Rossiter, David; Burke Wood, Patricia (Electronic version published by Vancouver Island University, 2017)
Over the course of the last decade and a half, we have interrogated key intersections of the political economy of natural resource development and ongoing geographic strategies of colonialism in BC. Studying Gordon Campbell’s obstructionist referendum on treaty rights and his subsequent pivot to campaign for a “new relationship” taught us that reconciliation in the context of neoliberalism will necessarily be incomplete, particularly in the context of insecure provincial territorial sovereignty. Studying both Northern Gateway pipeline proponents’ discursive and legal strategies for fixing territory for the investment of capital and First Nations’ politics of refusal and assertions of sovereignty in the face of these strategies has reinforced and highlighted for us the fact that the BC polity rests upon an unstable material-ideological foundation of land and title arrangements. Underlying differences in understandings of property, and how these differences have been used to secure citizenship for some and undermine it for others, raise once more the fundamental question of what are desirable core geographical organizing principles for the relationship between indigenous peoples and settler society in Canada generally, and BC in particular? Our analyses of the (post)colonial geographies of lands and resources in BC suggest that unsettling British Columbia’s status quo will require reengagement with the foundational geographies envisioned by indigenous parties to treaties with settlers on Turtle Island though the metaphor of the two-row-wampum. https://viurrspace.ca/bitstream/handle/10613/4980/BCStudies2017ReferendumtoReconciliation_final.pdf?sequence=5&isAllowed=y Presentation given at (Un)settling British Columbia - BC Studies 2017 Conference. Conference date: May 4 - 6, 2017. Location: Vancouver Island University, Snuneymuxw First Nation Territory / Nanaimo, B.C.